New insights into lead ions activation for microfine particle ilmenite flotation in sulfuric acid system: Visual MINTEQ models, XPS, and ToF–SIMS studies. (15th August 2020) - Bai, Shaojun; Yu, Pan; Ding, Zhan; Bi, Yunxiao; Li, Chunlong; Wu, Dandan; Wen, Shuming
Graphical abstract: Highlights: Pb(NO3 )2 improved micro-fine ilmenite flotation recovery by~12% with NaOL at pH 5.5. ToF–SIMS technique was innovatively used to determine ilmenite surface properties. H2 SO4 promoted valence transitions of iron on ilmenite surfaces from Fe(II) to Fe(III). Pb 2+ ions enhanced adsorptions of molecule/colloid forms of oleate and PbOL complex. Abstract: Recovering microfine particle ilmenite using froth flotation is extremely challenging. In this study, the flotation behaviors of microfine particle (−38 μm) ilmenite untreated or treated with lead ions using sodium oleate as a collector were studied. Micro-flotation experiments revealed that the ilmenite presented superior floatability at pH 5.5. Pb(NO3 )2 increased the flotation recovery by~12%. Solution component analysis indicated that the presence of lead ions depressed the dissolution of Fe and Ti metal ions on the ilmenite surface. The dominant Pb(II) species and RCOOH(I) were responsible for ilmenite flotation. Zeta potential measurements suggested that the RCOOH (I) and RCOO − ions mainly reacted with Fe and Pb on the ilmenite surfaces through electrostatic effects in addition to chemical adsorption. Fourier-transform infrared spectroscopy analysis showed that the new PbOL complex was formed on the ilmenite surfaces. X-ray photoelectron spectroscopy confirmed that the treatment of sulfuric acid promoted the valence transitions of iron ions. The proportion of the surface covered by Fe 3+ eventually increased from 32.51% to 63.22%. Time-of-flight secondary ion mass spectrometry (ToF–SIMS) provided strong evidence for the increased adsorption of oleate species on the ilmenite surfaces. Accordingly, the intensity of C4 H7 + increased from 16, 447 to 21089. New insights into lead ions activation for microfine particle ilmenite flotation in sulfuric acid system were mainly attributed to the oxidization of SO4 2− ions and the reinforced absorption of molecule/colloid oleate and PbOL complex compounds.